In vitro effects of L-carnitine and glutamine on motility, acrosomal abnormality, and plasma membrane integrity of rabbit sperm during liquid-storage - Sariozkan, Serpil; Ozdamar, Saim; Turk, Gaffari; Canturk, Fazile; Yay, Arzu (Academic Press Inc Elsevier Science, 2014)
This study was designed to evaluate the in vitro effects of L-carnitine and glutamine (Gin) on the sperm quality parameters of liquid-stored rabbit semen maintained up to 24 h at 5 degrees C. Pooled and extended ejaculates were divided into two equal portions. L-Carnitine doses of 0.5, 1 and 2 mM were added to the first portion, and glutamine was added at the same doses to the second portion. All samples were cooled to 5 degrees C and examined at 0, 6, 12 and 24 h of liquid storage. Supplementation of the semen extender with three different doses of L-carnitine provided significant increases in the percentage of motile sperm at 12 h (P < 0.01), and 24 h (P < 0.001) and enabled significant protection of the sperm plasma membrane (P < 0.01) at 12 and 24 h of cool-storage, in comparison to the control samples. Only the 2 mM dose of L-carnitine significantly (P < 0.01) decreased the rate of acrosomal damage when compared to the control group. Furthermore, all doses of Gin caused a significant (P < 0.01) decrease in acrosomal damage at 6 h, and provided significant improvement (P < 0.01) in sperm motility, acrosomal and plasma membrane integrities at 12 and 24 h of liquid storage, when compared to the controls. In conclusion, the supplementation of liquid-stored rabbit semen with L-carnitine and Gln provided a protection for sperm against cool storage-induced functional and structural damages. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Rabbit; Spermatological parameters; L-Carnitine; Glutamine; Liquid storage